The Impact of the Covid-19 Pandemic on Student Learning Activities at Madrasah Ibtidaiyah - Suhaimi, Suhaimi; Saidah, Saidah; Rahman, Rashid; Idris, Haziq (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
In 2019, the Covid-19 virus emerged, causing all work to be done online, including the learning process. The Covid-19 pandemic greatly disrupted normal learning activities, making it a new thing in the world of education. The purpose of this study was to determine the impact of Covid-19 on student learning activities at Madrasah Ibtidahiyah. This study uses a quantitative method using a survey model and in-depth interviews. The survey used in this study was online-based. The results of this study indicate that student understanding decreases during learning activities during Covid-19, so teachers must know what kind of learning model will be carried out during that period so that student achievement and interest in learning do not decrease. The conclusion of this study explains that due to the impact of Covid-19 on learning activities, student motivation has decreased so that many student achievements are not in accordance with school needs. Therefore, the limitation of this study is that this researcher only conducted research on the impact of the Covid-19 pandemic on student learning activities at Madrasah Ibtidaiyah, the researcher hopes that further researchers can conduct research on solutions on how to overcome the impact of the Covid-19 pandemic on student learning activities.